KADAR Na+, K+, Cl-, DAN KALSIUM TOTAL SERUM DARAH SERTA HUBUNGANNYA DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - ANGGRAINI, PUSPITA; RUSDI, RUSDI; ILYAS, ERMITA IBRAHIM (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Hypertension is currently still a major problem in the world. In Indonesia, the number of hypertension tends to increase every year. One of the causes of hypertension is high salt consumption. This research was held to identify levels of Na+, K+, Cl- and total calcium in blood serum and to analyze the relationship among levels of Na+, K+, Cl- and total calcium with blood pressure. This study was conducted on March to May 2014 using a Crosssectional method. The result showed that Na+ level in hypertensive patient significantly higher compared in normotensive (p=0.000). K+ level in hypertensive patient significantly lower than normotensive (p=0.002). In addition, no significant between Cl- level (p=0.514) and total calcium level (p=0.417) in hypertensive patients and normotensive subject. There was a significant relationship between Na+ level with systolic blood pressure (rs=0.419) and diastolic blood pressure (rs= 0.455). There was a significant relationship between K+ level with systolic blood pressure (rs=-0.403) and diastolic (rs=-0.496). There was no significant relationship between Cl- level with systolic blood pressure (rs=0.071) and diastolic (rs=0.092). There was significant relationship between total calcium level with systolic blood pressure (rs=-0.393) and no significant with diastolic (rs=-0.306). In conclusion, there were significant differences in the level of Na+ and K+ in hypertensive patient and normotensive and a significant relationship among level of Na+ and K+ with blood pressure. There were no significant differences in the levels of Cl- and total calcium in hypertensive patient and normotensive and no significant relationship among levels of Cl- and total calcium with blood pressure. Key Words: blood pressure, Cl-, hypertension, K+, Na+, total calcium